EGAP or ESAP? Towards meeting the academic English Language needs of Undergraduates - Soo, Ruey Shing; Tam, Shu Sim; Taher, Bahrani (Academic Journal INC, 2013)
“Needs analysis” is an important stage in language curriculum design as learners‟ language needs in the target literacy contexts can be determined. Nonetheless, many higher learning institutions overlook this component and hastily jump into designing a language course on an ad hoc basis due to the hassles of conducting it and a lack of awareness of needs analysis as a tool in curriculum development. The findings of this study offer a potential solution for institutions with similar contexts. Drawing upon two comprehensive needs analysis approaches – Target Situation Analysis and Present Situation Analysis, this study investigates the academic English language needs and language ability of the pre-university students at The University of Selangor, Malaysia. Data from multiple perspectives: students, ESL (English as a Second Language) lecturers and subject lecturers were collected via three sets of questionnaires. Empirical evidence indicates that the students had greater difficulty with the language rather than the content of subject matters. Besides that, another interesting finding is the differing opinions between the ESL and subject lecturers regarding the students‟ ability in handling writing and listening tasks. The results also indicate that English for Specific Academic Purposes (ESAP) courses are more suitable to fulfil the students‟ current learning needs as compared to English for General Academic Purposes (EGAP) courses. These findings have implications on curriculum planning and review, materials development and implementation of teaching methods.